Integrated care effectiveness for adults with co-occurring disorders. Issue 1 (23rd December 2020) - Mooss, Angela; Myatt, Joyce; Goldman, Jennifer; Alexander, Joey-Ann
Abstract : Purpose: This study examined effectiveness of an integrated care program on emergency department visits within a longitudinal sample of patients with both primary care and behavioral health diagnoses. Design/methodology/approach: Patients with co-occurring disorders enrolled in an integrated care clinic and were followed over time to determine whether participation in the clinic, including engagement in wellness/peer services, predicted decreases in Emergency Department (ED) use. Associations between socio-demographic characteristics of patients and ED use were also analyzed. Findings: After 6 months, clinic patients had decreases in ED use that continued for twelve months, albeit to a lesser degree. Demographics and program services were not related to ED use; however, multiple associations existed between high ED utilizers, severe mental illness (SMI), substance use disorders (SUD) and non-retention in services. Research limitations/implications: The study lacked a comparison group and there was no distinction between avoidable and unavoidable ED visits. A small sample size across time points led to inconclusive post hoc findings. Originality/value: This study explored effectiveness of primary care integration into a behavioral health clinic for persons with multiple morbidities. Although initial decreases in ED visits were present, results indicate that these models may not be effective for persons with SMI or SMI/SUD who are already high ED users. This study provides support for integrated care in reducing ED use among persons with multiple morbidities and calls for further research on designing effective integrated models for persons with SMI and SUD.